2018
DOI: 10.1109/tbme.2017.2707344
|View full text |Cite
|
Sign up to set email alerts
|

Event-Triggered Model Predictive Control for Embedded Artificial Pancreas Systems

Abstract: Our proposed framework integrated seamlessly with a wide variety of popular MPC variants reported in AP research, customizes tradeoff between glycemic regulation and efficacy according to prior design specifications, and eliminates judicious prior selection of controller sampling times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…In Laguna Sanz et al [24], a confidence index was incorporated in a zone MPC to allow controller parameter adaptation based on the accuracy of the prediction model in recent history. An MPC with event-triggered controller update strategies was proposed by Chakrabarty et al [25] to reduce energy consumption of an embedded AP while maintaining satisfactory glucose regulation performance. A recent review of adaptive approaches to AP design can be found in Turksoy and Cinar [26].…”
Section: Introductionmentioning
confidence: 99%
“…In Laguna Sanz et al [24], a confidence index was incorporated in a zone MPC to allow controller parameter adaptation based on the accuracy of the prediction model in recent history. An MPC with event-triggered controller update strategies was proposed by Chakrabarty et al [25] to reduce energy consumption of an embedded AP while maintaining satisfactory glucose regulation performance. A recent review of adaptive approaches to AP design can be found in Turksoy and Cinar [26].…”
Section: Introductionmentioning
confidence: 99%
“…There are several biological functions which use feedback control and control methodologies are increasingly being used in non-standard applications [57]. These non-standard applications include climate control [29], biological systems [54], economics [47], resource management [35] and medical treatments [7].…”
Section: Systems and Control Theory For Persuasionmentioning
confidence: 99%
“…It provides a systematic way of determining inputs in the presence of noise and uncertainty. Techniques from control theory are increasingly being used for interdisciplinary applications such as climate control, economics, and for medical treatments [7,29,47,57]. It has been suggested that methods from control theory could help determine rules for adaptive digital interventions [3, 10-12, 30, 42-44, 55].…”
Section: Introductionmentioning
confidence: 99%
“…Several control algorithms are proposed for AP systems, including proportional-integralderivative control [14][15][16][17][18][19][20][21][22], fuzzy logic control [23][24][25] and model-based predictive controllers such as model predictive control (MPC) [26][27][28][29][30][31][32][33] and generalized predictive control [34][35][36][37][38]. MPC is widely employed in AP systems because of its inherent ability to easily and effectively handle complex systems with control constraints and many input and output variables.…”
Section: Introductionmentioning
confidence: 99%